Underwater repair of fatigue cracks by gas tungsten arc welding process - Rodriguez-Sanchez, J. E.; Perez-Guerrero, F.; Liu, S.; Rodriguez-Castellanos, A.; Albiter-Hernandez, A. (Fatigue & fracture of engineering materials & structures, 2014)
ABSTRACT A fatigue crack repair method for offshore jacket tubular joints is presented. This method is applicable for fatigue cracks detected and sized by regular inspection techniques such as magnetic particle inspection up to a crack depth in the range of 5 mm. The main advantage of the method relies on its easy implementation allowing to be applied immediately after the crack is detected because equipment required is easy to transport and operate; so, it can be on board of a regular inspection campaign ship. A welding procedure specification has to be prepared and qualified prior to implementation of the repair method, considering particular parameters of the jacket fleet and selecting the welding equipment to be used. The proposed method could reinstall the original fatigue life in early stages of growth avoiding the need of more expensive procedures of repair such as joint clamping.